2011
DOI: 10.1159/000324052
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cervical Cytology in the Diagnosis of Uterine Papillary Serous Carcinoma: Earlier Detection of a Poor Prognostic Cancer Subtype

Abstract: Objective: Early detection of uterine papillary serous (UPSC), clear cell (CCC), and grade 3 endometrioid carcinomas (G3EC) – all poor prognostic variants of endometrial carcinoma (EC) – is of particular clinical relevance. The study objective was to assess the utility of liquid-based cytology (Pap) in the detection of high-grade EC. Study Design: A retrospective, two-institution analysis of patients diagnosed with UPSC, CCC, or G3EC with a preoperative Pap from 1999 to 2010 was conducted. Results: One hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Skaznik-Wikiel et al [12 ]indicated that 25% of the Pap smears in 28 patients with ECCC were abnormal in their study assessing the utility of liquid-based Pap smears in the diagnosis of high-grade endometrial cancers. The incidence of abnormal Pap smears using conventional cytology was 52.3% (n = 11/21) in our study, which is higher compared to previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Skaznik-Wikiel et al [12 ]indicated that 25% of the Pap smears in 28 patients with ECCC were abnormal in their study assessing the utility of liquid-based Pap smears in the diagnosis of high-grade endometrial cancers. The incidence of abnormal Pap smears using conventional cytology was 52.3% (n = 11/21) in our study, which is higher compared to previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly differentiated EMCA and papillary serous adenocarcinoma are easier to detect on Pap smears as these are usually associated with high cellularity, with three-dimensional or papillary groups comprised of cells showing nuclear pleomorphism, irregularly distributed granular chromatin and macronucleoli [19,23]. The cytoplasm is usually finely vacuolated and the nuclei are eccentrically located within the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 10 women with high-grade uterine cancer who had preoperative Pap smears, 51.5% had USC, and significantly more patients with USC had abnormal cervical cytology (65.7%) than those with clear cell carcinoma (25%) or grade 3 endometrioid carcinoma (23.8%; p b 0.001) [41]. An abnormal Pap smear was the only presenting clinical finding in a significant number of asymptomatic USC patients (26.9%) compared with 4% of patients with clear cell carcinoma (CC) and grade 3 endometrioid carcinoma (p = 0.005).…”
Section: Diagnosismentioning
confidence: 99%